Biofoams with untapped enzymatic potential produced from beer bagasse by indigenous fungal strains - Aguirre Pranzoni, Celeste Beatriz (2024)
White rot fungi are promising organisms for the production of mycelial-based biofoams, providing a sustainable means of valorizing lignocellulosic wastes. This study explores the utilization of two indigenous fungal species, isolated from Argentina and belonging to the genera Trametes, for producing biofoams from brewery waste. The resulting biofoams exhibited an average density of 0.30 g cm−3, a Young’s modulus of approximately 1 MPa, and a compressive stress of around 19 MPa. Additionally, the variation of laccase activity throughout the biofoam production process was evaluated. Surprisingly, residual laccase activity was detected in the biofoams following oven drying at temperatures of 60, 80, and 100 °C. This detection highlights the untapped enzymatic potential of the biofoams and positions them as promising green catalysts for various biotechnological applications.